Livestock Master Plan guides public and private investments in Ethiopia to lift more than 2 million households out of poverty - CGIAR Research Program on Livestock (2017)
Livestock researchers and partners used their modelling expertise to provide a guide for public and private investments in Ethiopia, with the objective of reducing poverty; achieving food and nutritional security; contributing to economic growth, exports and foreign exchange earnings; and contributing to climate mitigation and adaptation. This roadmap, or master plan, was then used by various actors including the World Bank to shape their investments, which will ultimately impact more than 2.3 million of Ethiopia’s 11 million livestock-keeping households.